Teaching undergraduate psychology students about mental health through student-led case studies: a case example of the celebrity Spike Milligan. Issue 3 (25th October 2021) - Husbands, Melissa; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to suggest that student-led case studies are an important way to learn about mental health problems and to highlight this by presenting a case study of the comedic genius Spike Milligan. Design/methodology/approach: Celebrities live their lives in the public eye. In recent years, many have talked about their struggles with mental health. This paper is based on a student-led case study of the celebrity Spike Milligan. Findings: This case study suggests one previously under-emphasised issue and argues that Spike Milligan's wartime experiences may have led to post-traumatic stress disorder. Second, that he may have developed neuro-inflammation, through contracting sandfly fever during the war. This could have been an additional trigger for bipolar disorder. Research limitations/implications: While this is a single case study, it draws on a wide variety of research sources to back up the arguments advanced. Practical implications: Student-led case studies provide a way of engaging students more actively with mental health problems. Social implications: Mental illness is complex, if not more complex, than physical health problems. Case studies of celebrities like Spike Milligan can help develop a public understanding of mental illness, as they already have a working knowledge about the person. Originality/value: The case study illustrates how Bipolar 1 disorder is a complex and unique condition and that every individual's illness has different predisposing characteristics. It suggests that student-led case studies are a helpful learning tool.